Blockchain in Accounting and Auditing: A Systematic Literature Review - Moktar, Noraini; Deli, Mazzlida Mat; Jamil, Ainul Huda (Research in Accounting Journal (RAJ), 2025)
The rapid development of blockchain technology has generated significant discussion regarding its transformative potential in accounting and auditing. While blockchain offers features such as immutability, decentralization, and real-time verification, its actual impact on financial reporting quality and audit practices remains fragmented across the literature. This study aims to systematically review and synthesize scholarly research on blockchain applications in accounting and auditing over the period 2016–2026. Using a PRISMA-guided systematic literature review approach, peer-reviewed journal articles were identified, screened, and analyzed through thematic synthesis and qualitative content analysis. The findings reveal five dominant research streams: (1) blockchain and financial reporting quality, (2) audit transformation and risk reconfiguration, (3) governance and regulatory challenges, (4) crypto-asset accounting issues, and (5) technological integration with artificial intelligence and data analytics. The review indicates that blockchain enhances structural transparency and transaction traceability, potentially reducing detection risk in auditing. However, improvements in reporting quality are conditional upon regulatory clarity, governance mechanisms, and institutional readiness. Rather than eliminating audit risk, blockchain redistributes risk toward system integrity, cybersecurity, and smart contract reliability. This study contributes by integrating fragmented findings into a coherent analytical framework, identifying empirical gaps, and proposing a structured future research agenda. The results provide theoretical implications for digital accounting scholarship and practical insights for auditors, regulators, and policymakers navigating blockchain-enabled financial ecosystems.